Limitations of radiosensitization by direct telomerase inhibition to treat high-risk medulloblastoma - Sengupta, Satarupa; Senthil Kumar, Shiva; Bondra, Kathryn; Sobo, Matthew; Mo, Xiaokui; Drissi, Rachid (Frontiers in Oncology, 2023)
Medulloblastoma (MB) is the most common malignant pediatric brain tumor. Previous studies have elucidated the genomic landscape of MB leading to the recognition of four core molecular subgroups (WNT, SHH, group 3 and group 4) with distinct clinical outcomes. Group 3 has the worst prognosis of all MB. Radiotherapy (RT) remains a major component in the treatment of poor prognosis MB but is rarely curative alone and is associated with acute and long-term toxicities. A hallmark of cancer cells is their unlimited proliferative potential which correlates closely with telomere length. The vast majority of malignant tumors activate telomerase to maintain telomere length, whereas this activity is barely detectable in most normal human somatic tissues, making telomerase inhibition a rational therapeutic target in the setting of cancer recurrence and therapy resistance. We and others have previously shown that short telomeres confer sensitivity to ionizing radiation (IR) suggesting that telomerase inhibition mediated telomere shortening will improve the efficacy of RT while minimizing its side effects. Here, we investigated the efficacy of the combination of IR with IMT, a potent telomerase inhibitor, in an in vivo model of group 3 MB. Our results indicate that although IMT inhibited MB telomerase activity resulting in telomere shortening and delayed tumor growth, the combination with IR did not prevent tumor recurrence and did not improve survival compared to the treatment with IR alone. Together, these findings suggest that the radiosensitization by direct telomerase inhibition is not an effective approach to treat high-risk pediatric brain tumors.